R. Jakobson as Mediator of Cultural Transfer between Linguistics and Literary Experiments - Feshchenko, Vladimir (Przegląd Wschodnioeuropejski, 2018)
The article analyzes one of the forms of nomadism in the intellectual world, which is called cultural transfers. One of the directions in the study of cultural transfers is the migration of concepts and notions between scientific knowledge (in this case linguistic) and literary experience (mainly experimental). The article is devoted to one of such migration trajectory from the perspective of interdiscourse methodology. We discuss the works of one of the agents of cultural transfer in the field of linguistics – R. Jakobson. The task of the article is to draw a trajectory according to which the linguistic concepts of Jakobson intertwine with parallel processes in literary (mainly poetic) experiments. The analysis concludes that precisely in connection with close contexts and transfers between poetry and linguistics, the Russian science of language represented by Jakobson develops a view of literature as a special language and a special communicative system. This trend is not typical for the Anglo-American linguistic tradition of the twentieth century, the quintessence of which in the middle of the century was represented in the theories of N. Chomsky and his circle.